A comprehensive review of flexible cadmium telluride solar cells with back surface field layer - Ahmad N.I.; Kar Y.B.; Doroody C.; Kiong T.S.; Rahman K.S.; Harif M.N.; Amin N. (Elsevier Ltd, 2024)
Recent advancements in CdTe solar cell technology have introduced the integration of flexible substrates, providing lightweight and adaptable energy solutions for various applications. Some of the notable applications of flexible solar photovoltaic technology include building integrated photovoltaic systems (BIPV), transportation, aerospace, satellites, etc. However, despite this advancement, certain issues regarding metal and p-CdTe remained unresolved. Besides, the fabrication of a full-working device on flexible glass is challenging and requires special consideration due to the unstable morphology and structural properties of deposited film on ultra-thin glass substrates. The existing gap in knowledge about the vast potential of flexible CdTe solar cells on UTG substrates and their possible applications blocks their full capacity utilization. Hence, this comprehensive review paper exclusively concentrates on the obstacles associated with the implementation of CdTe solar cells on UTG substrates with a potential back surface field (BSF) layer. The significance of this study lies in its meticulous identification and analysis of the substantial challenges associated with integrating flexible CdTe onto UTG substrates and leveraging Cu-doped ZnTe as a potential BSF layer to enhance the performance of flexible CdTe solar cells. 2023 The Authors